Revolutionizing Fuel Cell Efficiency with Non-Metallic Catalysts for Oxygen Reduction Reactions - Zhang, Ruiquan; Zhang, Zhou; Chen, Qing; Hu, Maocong; Yao, Zhenhua (The Global Environmental Engineers, 2022)
Platinum-based catalysts are widely used in oxygen reduction reactions, but platinum’s high cost and low reserves have restricted their sustainable development. With continuous in-depth research, it has been found that metal-free catalysts also have better catalytic activity in oxygen reduction reactions and have great potential for development due to the low cost and abundant reserves of metal-free catalysts, which has become a hot research direction. This paper reviews the application of metal-free catalysts in oxygen reduction reactions, including heteroatom-doped carbon-based catalysts, polymeric nitrogen catalysts, and emerging carbon catalysts. This work provides insights into developing non-platinum catalysts for oxygen reduction reactions by comparing the catalytic activity, selectivity, and prolonged stability.